Nanoscale Hybrid Amorphous/Graphitic Carbon as Key Towards Next‐Generation Carbon‐Based Oxidative Dehydrogenation Catalysts - Herold, Felix (Angew Chem Int Ed Engl, 2021)
A new strategy affords “non‐nano” carbon materials as dehydrogenation catalysts that perform similarly to nanocarbons. Polymer‐based carbon precursors that combine a soft‐template approach with ion adsorption and catalytic graphitization are key to this synthesis strategy, thus offering control over macroscopic shape, texture, and crystallinity and resulting in a hybrid amorphous/graphitic carbon after pyrolysis. From this intermediate the active carbon catalyst is prepared by removing the amorphous parts of the hybrid carbon materials via selective oxidation. The oxidative dehydrogenation of ethanol was chosen as test reaction, which shows that fine‐tuning the synthesis of the new carbon catalysts allows to obtain a catalytic material with an attractive high selectivity (82 %) similar to a carbon nanotube reference, while achieving 10 times higher space–time yields at 330 °C. This new class of carbon materials is accessible via a technically scalable, reproducible synthetic pathway and exhibits spherical particles with diameters around 100 μm, allowing unproblematic handling similar to classic non‐nano catalysts.